Factors to be considered in putting a price on an artwork / Irwan Hj. Othman and Rodey Hamza Hamzah - Othman, Irwan; Hamzah, Rodey Hamza (Unit Penerbitan Universiti Teknologi MARA, Kelantan, 2017)
Understanding how the price of artworks is priced usually becomes a conflict in the field of arts. This is because some parties do not know how to put a price on certain artworks. Artists, audience, art enthusiasts and art collectors encounter this problem when putting the price if they do not understand how the price should be put on an artwork. Therefore, this article attempts to unravel how an artwork is placed a price to shed light on this concept. This article will help the parties involved in the related field to easily understand how the price is assessed and placed on the artworks. Therefore, the findings of this study will help the parties involved in putting the price of artworks. This writing will also unravel how an artwork is valued and how an artist raised his status as a successful artist.